Solid–State Hydrogen Storage Materials with Excellent Selective Hydrogen Adsorption in the Presence of Alkanes, Oxygen, and Carbon Dioxide by Atomic Layer Amorphous Al2O3 Encapsulation - Bu, Fanqi; Wang, Zhenyu; Wajid, Ali; Zhai, Rui; Liu, Ting; Li, Yaohua; Ji, Xin; Liu, Xin; Ding, Shujiang; Cheng, Yonghong; Zhang, Jinying (Nano-Micro Letters, 2025)
Metal hydrides with high hydrogen density provide promising hydrogen storage paths for hydrogen transportation. However, the requirement of highly pure H2 for re-hydrogenation limits its wide application. Here, amorphous Al2O3 shells (10 nm) were deposited on the surface of highly active hydrogen storage material particles (MgH2–ZrTi) by atomic layer deposition to obtain MgH2–ZrTi@Al2O3, which have been demonstrated to be air stable with selective adsorption of H2 under a hydrogen atmosphere with different impurities (CH4, O2, N2, and CO2). About 4.79 wt% H2 was adsorbed by MgH2–ZrTi@10nmAl2O3 at 75 °C under 10%CH4 + 90%H2 atmosphere within 3 h with no kinetic or density decay after 5 cycles ( 100% capacity retention). Furthermore, about 4 wt% of H2 was absorbed by MgH2–ZrTi@10nmAl2O3 under 0.1%O2 + 0.4%N2 + 99.5%H2 and 0.1%CO2 + 0.4%N2 + 99.5%H2 atmospheres at 100 °C within 0.5 h, respectively, demonstrating the selective hydrogen absorption of MgH2–ZrTi@10nmAl2O3 in both oxygen-containing and carbon dioxide-containing atmospheres hydrogen atmosphere. The absorption and desorption curves of MgH2–ZrTi@10nmAl2O3 with and without absorption in pure hydrogen and then in 21%O2 + 79%N2 for 1 h were found to overlap, further confirming the successful shielding effect of Al2O3 shells against O2 and N2. The MgH2–ZrTi@10nmAl2O3 has been demonstrated to be air stable and have excellent selective hydrogen absorption performance under the atmosphere with CH4, O2, N2, and CO2. Highlights: 1 Gas selective amorphous Al2O3 encapsulation was constructed on highly reactive MgH2 using atomic layer deposition. 2 Hydrogen selective adsorption was achieved in the impure hydrogen atmosphere containing impurities (O2, N2, CH4, and CO2). 3 Excellent air stability with no MgO or Mg(OH)2 generated after 3 months of air exposure was achieved.